Cracking the Copyright Dilemma in Software Preservation: Protecting Digital Culture through Fair Use Consensus - Butler, Brandon; Aufderheide, Patricia; Jaszi, Peter; Cox, Krista (Journal of Copyright in Education & Librarianship, 2019)
Copyright problems may inhibit the crucially important work of preserving legacy software. Such software is worthy of study in its own right because it is critical to accessing digital culture and expression. Preservation work is essential for communicating across boundaries of the past and present in a digital era. Software preservationists in the United States have addressed their copyright problems by developing a code of best practices in employing fair use. Their work is an example of how collective action by users of law changes the norms and beliefs about law, which can in turn change the law itself insofar as the law takes account of community norms and practices. The work of creating the code involved facilitators who are communication, information sciences, and legal scholars and practitioners. Thus, the creation of the code is also an example of crossing the boundaries between technology and policy research.